Mussolini's intellectuals : fascist social and political thought - Gregor, A. James (Anthony James), 1929- (Princeton University Press, 2005)
Fascism has traditionally been characterized as irrational and anti-intellectual, finding expression exclusively as a cluster of myths, emotions, instincts, and hatreds. This intellectual history of Italian Fascism--the product of four decades of work by one of the leading experts on the subject in the English-speaking world--provides an alternative account. A. James Gregor argues that Italian Fascism may have been a flawed system of belief, but it was neither more nor less irrational than other revolutionary ideologies of the twentieth century. Gregor makes this case by presenting for the fir.